The chelation of metal ions by the acylpolyamine toxins from the web-spider Nephilengys cruentata: effects in the intoxication/detoxification of preys - de Fatima Manzoli-Palmas, Maria; Gobbi, Nivar; Palma, Mario Sergio [UNESP] (Birkhauser Verlag Ag, 2006)
Orb-web-spiders present a series of different strategies for prey capture, involving the use of different types of silk for web building, the use of adhesive traps in the webs, the secretion of toxic compounds to the spider's preys in the adhesive coating of the capture web and the biosynthesis of a wide range of structurally related acylpolyamine toxins in their venoms. The polyamine toxins usually block neuromuscular junctions and/or the central nervous system (CNS) of Arthropods, targeting specially the ionotropic glutamate receptors; this way these toxins are used are as chemical weapons to kill / paralyze the spider's prey. Polyamine toxins contain many azamethylene groups involved with the chelation of metal ions, which in turn can interact with the glutamate receptors, affecting the toxicity of these toxins. It was demonstrated that the chelation of Ni+2, Fe+2, Pb+2, Ca+2 and Mg+2 ions by the desalted crude venom of Nephilengys cruentata and by the synthetic toxin JSTX-3, did not cause any significant change in the toxicity of the acylpolyamine toxins to the model-prey insect (honeybees). However, it was also reported that the chelation of Zn+2 ions by the acylpolyamines potentiated the lethal / paralytic action of these toxins to the honeybees, while the chelation of Cu+2 ions caused the inverse effect. Atomic absorption spectrometry and Plasma-ICP analysis both of N.cruentata venom and honeybee's hemolymph revealed that the spider's venom concentrates Zn+2 ions, while the honeybee's hemolymph concentrates Cu+2 ions. These results are suggesting that the natural accumulation of Zn+2 ions in N. cruentata venom favors the prey catching and/or its maintenance in the web, while the natural accumulation of Cu+2 ions in prey's hemolymph minimizes the efficiency of the acylpolyamine toxins as killing/paralyzing tool.
Keywords: acylpolyamine toxins; spider venom; neurotoxicity; metal ion chelation; lethality; paralysis